TREND WISATA KULINER TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN KE KAWASAN KULINER CIHAPIT - Ghini Kuntala Devi; Surya Aditya Wahyono; Ita Karnita; Sara Rabasari (Journal of Innovation Research and Knowledge, 2025)
The Cihapit area in Bandung is known as a culinary center that attracts many visitors, both locals and tourists. Along with the development of the culinary industry, this area is increasingly becoming one of the main destinations for food lovers. However, more than just a place to enjoy a meal, the culinary trends that develop in Cihapit also have a major influence on the decision to buy food in the area. The data analysis technique used is qualitative data analysis. The authors decided to conduct population research on culinary tourism in Cihapit, which amounted to 2108 people with 95 respondents and the sampling technique used was non-probability sampling. The target achievement in this research is published in the national accreditation journal Sinta 3. The TKT that will be generated is at level 2 because this research can answer research hypotheses, research instruments, research designs have been traced